Prevalência de Toxoplasma gondii e neospora spp. e análise dos fatores de risco em equídeos do sudeste do Brasil - Oliveira, Patrícia Magalhães de (2014)
This study evaluated the prevalence and analysis of risk factors for Neospora spp. and Toxoplasma gondii in horses (horses, mules and ponies), within rural and urban areas of Uberlândia. Serum samples from 257 horses were evaluated for the presence of antibodies against Neospora spp.e T. gondii by the indirect immunofluorescence assay (IFA) and molecular diagnosis by the method of polymerase chain reaction (PCR). In addition, a survey was conducted to evaluate the possible risk factors (genetic group, age, gender, economic activity, history of miscarriage, contact with domestic and wild animals and ECC). Of 257 blood samples evaluated, 13.2% (34/257) had a positive by IIF for Neospora spp. PCR and the overall prevalence of 1.2% (3/257) was found. There was a significant difference when comparing the frequency of positive animals between techniques. Of the factors studied, age was considered a risk factor for Neospora spp. Compared to Toxoplasma gondii, 9.7% (25/257) had a positive by IIF, and PCR were 10.9% (28/257). When comparing rural and urban areas, only the PCR was no statistically significant difference. By IIF only gender and age were risk factors. On the PCR technique, the only significant risk factor was the genetic group. Therefore, it is concluded that there is a T. gondii and Neospora spp. distributed throughout the city of Uberlândia and its prevalence is independent of rural or urban area. Being the genetic group, age and gender considered risk factors for Toxoplasma gondii and Neospora spp age for.